2018
DOI: 10.3310/phr06050
|View full text |Cite
|
Sign up to set email alerts
|

The health impacts of energy performance investments in low-income areas: a mixed-methods approach

Abstract: BackgroundCold homes and fuel poverty contribute to health inequalities in ways that could be addressed through energy efficiency interventions.ObjectivesTo determine the health and psychosocial impacts of energy performance investments in low-income areas, particularly hospital admissions for cardiorespiratory conditions, prevalence of respiratory symptoms and mental health status, hydrothermal conditions and household energy use, psychosocial outcomes, cost consequences to the health system and the cost util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 235 publications
(235 reference statements)
3
58
1
2
Order By: Relevance
“…Improvements to indoor temperature may also affect the psychosocial pathway, by improving householder perception of his home, reinforcing social interaction with family and friends, based on the increasing use of his house. For instance, Poortinga et al [29] have reported evidence that improvements to indoor temperatures were associated with increased use of more rooms in the house, enabling frequent visits from relatives and friends.…”
Section: Relevance Of Housing Energy Efficiency For Health Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Improvements to indoor temperature may also affect the psychosocial pathway, by improving householder perception of his home, reinforcing social interaction with family and friends, based on the increasing use of his house. For instance, Poortinga et al [29] have reported evidence that improvements to indoor temperatures were associated with increased use of more rooms in the house, enabling frequent visits from relatives and friends.…”
Section: Relevance Of Housing Energy Efficiency For Health Outcomesmentioning
confidence: 99%
“…building envelope-indoor temperature [27,29,40,44,[46][47][48] Energies 2020, 13, x FOR PEER REVIEW 7 of 23…”
Section: Analysis Of Direct and Indirect Links Between Indoor Temperamentioning
confidence: 99%
See 3 more Smart Citations